2016
DOI: 10.1155/2016/2593698
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Frequency of Cyclists’ Red-Light Running Behavior Using Bayesian PG Model and PLN Model

Abstract: Red-light running behaviors of bicycles at signalized intersection lead to a large number of traffic conflicts and high collision potentials. The primary objective of this study is to model the cyclists’ red-light running frequency within the framework of Bayesian statistics. Data was collected at twenty-five approaches at seventeen signalized intersections. The Poisson-gamma (PG) and Poisson-lognormal (PLN) model were developed and compared. The models were validated using Bayesianpvalues based on posterior p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Comparing the behaviour differences between e-bike cyclists and traditional cyclists, studies show that e-bikes cyclists would gain higher mobility at the expense of more risk behaviour (Bai et al 2013;Cherry, Cervero 2007). Several scholars found that the factors causing behaviour differences are age, gender and stages of signal phase (Wu et al 2012(Wu et al , 2016Guo et al 2014). Xu et al (2016) identified the interrelationships of these factors and proposed a method to evaluate safety of nonmotorized lanes.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the behaviour differences between e-bike cyclists and traditional cyclists, studies show that e-bikes cyclists would gain higher mobility at the expense of more risk behaviour (Bai et al 2013;Cherry, Cervero 2007). Several scholars found that the factors causing behaviour differences are age, gender and stages of signal phase (Wu et al 2012(Wu et al , 2016Guo et al 2014). Xu et al (2016) identified the interrelationships of these factors and proposed a method to evaluate safety of nonmotorized lanes.…”
Section: Introductionmentioning
confidence: 99%